The History of the Emergence of Islamic Institutions: Between Authenticity and Modernity - Saadi, Samyan Abdulkhaleq (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The development of administrative thought and its applications has been linked since the beginning of creation to man's need for food, drink, shelter, protection from the vagaries of nature, and defense of himself. Since people have lived in groups since ancient times, administration has been important in human life, and the administrative process has been the criterion that differentiates between what is known as organized societies and those that live a jungle life. The history of humanity confirms to us the importance of management in the emergence of human civilization and the progress it has achieved, and thus it is linked to successive human civilizations. Therefore, the emergence and development of administration from ancient times until modern history will be reviewed here, through three stages: the first is the period before Christ, the second is the period after Christ, and the last is the period of contemporary history.